TERJEMAH DARI MASA KE MASA (SEBUAH TELAAH HISTORIS TEORI TERJEMAH BAHASA ARAB) - Amin, Nur Fadilah; Abu Nawas, Kamaluddin; Hamzah, Andi Abdul (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2023)
The concept of translation is generally described as an activity of transferring information from one language to another with the aim that people who read in the target language can easily understand what is conveyed. Therefore, the translation process itself must consist of at least three components: source language (Bsu), target language (Bsa), and information. History records that the main period of translation coincided with the time when there were differences between two cultures and two languages, especially in the spread of science and culture. From its own history, the process of translation occurs because of a need, whether it is cultural, economic, scientific, religious, or even because of the language motive itself. Periodization in the history of Arabic translation began before the Prophet Muhammad was sent, and the peak can be seen during the Khalifah Abbasiyah with the establishment of Baitul Hikmah. Some of the pioneering figures of Arabic translation are: Al-Harith bin Kaldah, Khalid bin Yazid bin Muawiyah, Hunain Bin Isaac, Yahya Bin Addi, Qistha Bin Luqa Al-Ba'labaki, Abu Usman Al-Dimasyqa, Yohana Bin Al-Bathriq, Ibn Al-Muqaffa, and Al-Jahiz.Keywords: Theory, Translation, History, Arabic LanguageKonsep menerjemahkan secara umum digambarkan sebagai suatu kegiatan memindahkan informasi dari satu bahasa ke bahasa yang lain dengan tujuan agar orang yang membaca dengan menggunakan Bahasa sasaran mampu memahami dengan mudah apa yang disampaikan. Sehingga proses penerjemahan sendiri minimal harus terdiri dari tiga komponen yaitu bahasa sumber (Bsu), bahasa sasaran (Bsa) dan informasi. Sejarah mencatat bahwa periode utama terjemah bersamaan dengan zaman terdapatnya perbedaan antara dua budaya dan dua bahasa, khususnya dalam penyebaran ilmu pengetahuan dan budaya. Dari sejarahnya sendiri, proses penerjemahan terjadi karena suatu kebutuhan, baik yang bersifat kebudayaan, ekonomi, ilmu pengetahuan, agama atau bahkan karena motif bahasa itu sendiri. Periodisasi dalam sejarah penerjemahan bahasa Arab pun dimulai sebelum Rasululullah SAW diutus, dimana puncaknya dapat kita lihat pada masa Khilafah Abbasiyah dengan didirikannya Baitul Hikmah. Adapun beberapa tokoh-tokoh pelopor terjemah Arab yaitu: Al-Harits bin Kaldah, Khalid bin Yazid bin Muawiyah, Hunain Bin Ishak, Yahya Bin Addi, Qistha Bin Luqa Al-Ba’labaki, Abu Usman Al-Dimasyqa, Yohana Bin Al-Bathriq, Ibnu Al-Muqaffa’ dan Al-Jahiz.Kata Kunci: Teori, Terjemah, Histori, Bahasa Arab